Mental health among pregnant women: a comparative study between primi and multigravida subjects - Sharma, Hemlata; Sharma, Shikha (International Journal Of Community Medicine And Public Health, 2022)
Background: Worldwide about 10% of pregnant women and 13% of women who have just given birth experience a mental disorder, primarily depression. In developing countries this is even higher, i.e. 15.6% during pregnant and 19.8% after child birth. As this study indicates the impact of pregnancy on mental health of antenatal women. Mental health during pregnancy has great significance not only for women but it may also impact a child's growth and psychological development recognizing the need of mental health care for antenatal women motivated present study. Aim of the study is to assess the mental health among the pregnant women. Methods: The research design used in this study is survey research design. The sample comprises of 90 women in primi and multigravida. The study was conducted in the department of gynaecology of Geetanjali Medical College and Hospital Udaipur, Rajasthan India. Results: Purposive randomized sampling was used to conduct the research appropriate test used to carry out the study. The result shows that mental health of multigravida is poor in comparison to primigravida. Conclusion: Study concludes that there is significant difference in the mental health of the subjects between the group of multigravida and primigravida and there is no significance difference in the mental health observed within the group of primi and multigravida subjects.